Zorro y sus amigos - Marshall, Edward; Marshall, James, 1942-1992.; Fiol., Maria A. (New York : Penguin Ediciones, 1996)
In three separate episodes Fox wants to play with his friends, but duty in one form or another interferes.
Translation of: Fox and his friends.
Keywords: Foxes -- Fiction; Brothers and sisters -- Fiction